2004
DOI: 10.1093/molehr/gah100
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of calcium-binding protein S100 in human uterine smooth muscle tumours

Abstract: S100 proteins belong to the EF-hand Ca(2+ )-binding protein family and regulate a variety of cellular processes via interaction with different target proteins. Several diseases, including cancer and melanoma, are related to the abnormal expression of S100 proteins, which are expressed in cell- and tissue-specific manners. We investigated the expression of S100 family members in human uterine smooth muscle tumours. Expression of six members of the S100 protein family: S100A1, A4, A6, A7, A10 and A11, was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…27 Recent investigations have emphasized the potential diagnostic and oncogenetic role of S100 proteins in a variety of tumors. [28][29][30][31][32][33][34] In this study, we found that S100A1 protein is expressed in renal oncocytomas, and in clear cell and papillary renal cell carcinomas but not in chromophobe renal cell carcinomas. We found significant statistical differences between S100A1 immunoexpression in clear cell and chromophobe renal cell carcinomas (Po0.001), which suggests that S100A1 could be a useful tool in their differential diagnosis.…”
Section: Discussionmentioning
confidence: 46%
“…27 Recent investigations have emphasized the potential diagnostic and oncogenetic role of S100 proteins in a variety of tumors. [28][29][30][31][32][33][34] In this study, we found that S100A1 protein is expressed in renal oncocytomas, and in clear cell and papillary renal cell carcinomas but not in chromophobe renal cell carcinomas. We found significant statistical differences between S100A1 immunoexpression in clear cell and chromophobe renal cell carcinomas (Po0.001), which suggests that S100A1 could be a useful tool in their differential diagnosis.…”
Section: Discussionmentioning
confidence: 46%
“…Conversely, S100A11 has been shown to be overexpressed in many different types of human cancer, including those derived from the esophagus (Ji et al, 2004), stomach (Oue et al, 2004), colorectum (Tanaka et al, 1995;Stulik et al, 1999), pancreas (Ohuchida et al, 2006), thyroid (Torres-Cabala et al, 2004), uterus (Kanamori et al, 2004), and soft tissues (Schaefer et al, 2004). Although the widely observed upregulation of S100A11 indicates that S100A11 may be involved in growth enhancement, malignant progression of cancer cells, or both, no mechanistic interpretation has been provided.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, S100A11 is considered a candidate tumor suppressor gene (12)(13)(14). In contrast, in cancer research, the widely observed up-regulation of S100A11 indicates that S100A11 may be involved in growth enhancement and/or malignant progression of cancer cells (15)(16)(17)(18)(19)(20)(21). This seems paradoxical and no reasonable interpretation has been provided in these studies (35).…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, S100A11 is now considered a strong tumor suppressor gene candidate (12)(13)(14). To test whether S100A11 has the potential to be a novel diagnostic biomarker, expression studies of the molecule have been performed in multiple human cancers such as gastric cancer (15), prostate cancer (16), esophageal carcinoma (17), pancreatic cancer (18,19), uterine leiomyoma (20) and colorectal cancer (21). These results have shown that the progression of cancer is related to high level expression of S100A11 in the tumor tissue, suggesting that S100A11 may be a novel diagnostic marker.…”
Section: Introductionmentioning
confidence: 99%